Data on Patient Record Trajectory for Linkage (DataPRinT Linkage). - Sumeet Kalia; Michelle Greiver; Frank Sullivan; Conrad Pow; Aziz Sheikh (International Journal of Population Data Science, 2022)
The linkage of Electronic Medical Records, Administrative and other data sources is highly valuable for research and health system monitoring. Once linked, combined resources can be analyzed to provide the answers to a variety of health questions that otherwise could not be answered. However, legislative and administrative barriers, including lengthy processes for data sharing agreements, may preclude timely linkage which is a key requirement during pandemics.